Le travail corporel dans le contexte des élections de Miss - Camille Couvry (Recherches Sociologiques et Anthropologiques, 2020)
The article attempts to analyse the displacements, in the experience of women having taken part in Miss contests, from body work carried out within the context of local level contests towards forms of aesthetic labour. Under what conditions can body work carried out in the context of contests support the access of women to remunerat-ed aesthetic labour? How does the associative context of Miss contests and their in-teractions involving body work support these dynamics? After having illustrated the women’s reappropriations of their experiences in contests into professional life, using concrete examples, the article provides an account of the socialisation of the body at work in the contests and of what the configuration of contests produces in terms of potential access to employment involving aesthetic labour. Access to a remunerated form of aesthetic labour is nevertheless contingent on the effects of class, gender and age. Moreover, if body work done within the contests represents a means of reinforc-ing body capital, it is not effective in every space of aesthetic labour. In addition, that body capital does not operate alone and its effectiveness in individual trajectories depends on other capital, in particular social and cultural.